THE EXISTENCE OF SURABI BANDUNG WITH A NEW TASTE - Setiabudiarto, Rizky Asyahri; Amalia, Almira; Nurmala, Nurmala (Community Services and Social Work Bulletin, 2023)
Serabi is a traditional snack originating from Indonesia. There are two types of Serabi, namely Serabi Solo and Surabi Bandung. Both types of Pancakes have different flavors and ingredients. Pancakes or soerabi are similar to pancakes. These typical Indonesian pancakes are usually associated with the city of Bandung or Solo. The main difference may lie in the main ingredients and various toppings. The author introduces Surabi in Tangerang which has various types of toppings. There is a Surabi Bandung restaurant which is no longer served with gravy, but served with various kinds of western-flavored toppings. Several restaurants in Tangerang serve Surabi with western topping variants. Therefore, we found 3 different restaurants in Tangerang, including Waroeng Bangpeh, Surabi Teras, and Rumah Surabi 74 Larangan. They serve delicious Surabi Bandung and various western toppings. This study aims to determine the background of the mixing of local and western cultures which can be seen from the food. Then, the writer wants to provide information related to Surabi's multiculturalism. In addition, readers get to know the cultural background of the seller or surabi maker. Researchers uses qualitative research methods. This research used an observation approach and interviews with informants. Researchers collected data by interviewing surabi sellers in three different shops in the Tangerang area, then we recorded data findings from informants. This research was conducted at the Surabi restaurant. The data collection process starts from giving questions to informants. Then data is collected by listening and recording all information related to the research problem.